Women Suffered More Than Men Both During and After the COVID‐19 Pandemic—A Cross‐Sectional Study Among 29,079 Patients With Type 2 Diabetes - Grethe Åstrøm Ueland; Tony Ernes; Tone Vonheim Madsen; Sverre Sandberg; Bjørn Olav Åsvold; Karianne Fjeld Løvaas; John Graham Cooper (Endocrinology, Diabetes & Metabolism)
ABSTRACT Objective To investigate the gender differences and the disparities between infected and noninfected patients with type 2 diabetes (T2D) regarding patient‐reported experiences during the COVID‐19 pandemic in Norway. Method Register study using questionnaires sent electronically to patients with T2D, June 2022. The questionnaire included 82 questions covering COVID‐19 disease, symptoms, medications, comorbidities, hospital care, possibility of working from home and information received from health authorities. Clinical and demographic data were collected from the Norwegian diabetes registry for adults. Results A total of 29,079 T2D patients participated, of whom 38.1% were women. Patients infected with COVID‐19 were younger, had shorter diabetes duration and less comorbidities than noninfected (p < 0.01). Women reported significantly more anxiety, depression and fear of not getting their diabetes medication than men did. Most patients were vaccinated against COVID‐19 (98.3%), whereas approximately 60% had received seasonal flu vaccine, and only 27.2% the pneumococcal vaccine. Women described more vaccine adverse effects and long Covid symptoms. Overall, 14% experienced vaccine complications and 27.3% of infected individuals reported long Covid symptoms. 2.4% of the infected patients needed hospital admission. Patients were satisfied with the follow‐up of their diabetes, and with information from the government during the pandemic. Conclusion Female patients were more likely to experience a prolonged Covid course, and higher degree of adverse effects from the COVID‐19 vaccine than male patients. Also, long Covid symptoms were significantly more often reported among female patients, while men were more prone to be hospitalised when infected. Hospitalised patients, both men and women, had significantly higher HbA1C than those who were not hospitalised. T2D patients had a surprisingly low pneumococcal vaccination coverage, despite recommendations in national guidelines.